A Literature Review: The Used of PROSPER Model in Guidance and Counseling Services for Improving Students Mental Health - Kristiana Firdausi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Internationally, in the past two decades, the issue of mental health has been the subject of discussion in the world health forum. Since 1946, at the International Health Conference, WHO released the definition of healthy humans as a condition in which an individual achieves "... not merely being free from disease, but capable of achieving physical, mental and social well-being." The definition has major consequences on the role of member states, including Indonesia, to put more effort in realizing the mental health of its people. One of the real efforts that can be done is to improve the mental health of students as the next generation of the nation, through guidance and counseling services based on the PROSPER model. The PROSPER model is a new scope in mental health, covering seven key elements that contribute to the realization of one's mental health namely: positivity, relationship, outcomes, strengths, purpose, engagement, and resilience. Guidance and Counseling teachers as promoters and students mental health facilitators, can integrate the PROSPER model in the program components that will be implemented. Thus, enriching content innovation regarding effective mental health, to realize smart and mentally healthy learners.